Repolarization abnormalities unmasked with exercise in sudden cardiac death survivors with structurally normal hearts. (7th December 2017) - Leong, Kevin M.W.; Ng, Fu Siong; Roney, Caroline; Cantwell, Christopher; Shun‐Shin, Matthew J.; Linton, Nicholas W.F.; Whinnett, Zachary I.; Lefroy, David C.; Davies, D. Wyn; Harding, Sian E.; Lim, Phang Boon; Francis, Darrel; et al.
Abstract: Background: Models of cardiac arrhythmogenesis predict that nonuniformity in repolarization and/or depolarization promotes ventricular fibrillation and is modulated by autonomic tone, but this is difficult to evaluate in patients. We hypothesize that such spatial heterogeneities would be detected by noninvasive ECG imaging (ECGi) in sudden cardiac death (SCD) survivors with structurally normal hearts under physiological stress. Methods: ECGi was applied to 11 SCD survivors, 10 low‐risk Brugada syndrome patients (BrS), and 10 controls undergoing exercise treadmill testing. ECGi provides whole heart activation maps and >1, 200 unipolar electrograms over the ventricular surface from which global dispersion of activation recovery interval (ARI) and regional delay in conduction were determined. These were used as surrogates for spatial heterogeneities in repolarization and depolarization. Surface ECG markers of dispersion (QT and Tpeak‐end intervals) were also calculated for all patients for comparison. Results: Following exertion, the SCD group demonstrated the largest increase in ARI dispersion compared to BrS and control groups (13 ± 8 ms vs. 4 ± 7 ms vs. 4 ± 5 ms; P = 0.009), with baseline dispersion being similar in all groups. In comparison, surface ECG markers of dispersion of repolarization were unable to discriminate between the groups at baseline or following exertion. Spatial heterogeneities in conduction were also present following exercise but were not significantly different between SCD survivors and the other groups. Conclusion: Increased dispersion of repolarization is apparent during physiological stress in SCD survivors and is detectable with ECGi but not with standard ECG parameters. The electrophysiological substrate revealed by ECGi could be the basis of alternative risk‐stratification techniques.